Library Electronic Scriptorium: A Contribution to the Research and Teaching of Philosophy, Letters, Identity and Culture - Ugalde Vìquez, Aracelly (2018)
The present work, which transcribes the project registered in the system of the National University academic formation, describes the first experiment used for management and control of the intellectual production of the Faculty of philosophy and letters, through the creation of a library and a repository for the purpose of identify, conserve and preserve the historical memory which is that academic work in the areas of knowledge have been studied and which are currently studying: philosophy, culture, literature, translation, Linguistics, librarianship, documentation, studies of gender, religion and society, ethics, human rights, Central American and Latin American studies.   That information had not been registered and was not available for viewing in the documentary collections in the collections of the libraries; In addition, was mostly scattered on desktops and in the houses of room, on shelves of the writers, mostly in printed format; and another, until on the memorabilia personal.